Modeling the effect of social interdependence in interprofessional collaborative learning. Issue 6 (2nd November 2022) - Shimizu, Ikuo; Kimura, Teiji; Duvivier, Robbert; van der Vleuten, Cees
ABSTRACT: Interprofessional education (IPE) often uses collaborative learning for better teamwork among multiple professions. Its theoretical background is social interdependence theory (SIT), and positive interdependence is key for successful collaborative learning. As there is little theoretical knowledge on how to optimize the social interdependence in IPE, educators often struggle to develop an effective program. Therefore, a more specific explanation of the relationship between social interdependence and interprofessional readiness might make IPE more effective. We aimed to elucidate how students' social interdependence in collaborative learning relates to interprofessional readiness. Health profession students (n = 259) undertaking a collaborative IPE program were asked to complete two validated questionnaires: Readiness for Interprofessional Learning Scale and Social Interdependence Scale in Collaborative Learning. A structural equation analysis provided a good fit for the data. Awareness of objectives positively predicted interprofessional collaboration and identity, whereas specific roles as health professionals negatively predicted interprofessional roles and identity. As the current healthcare system is highly specialized, there is a dilemma that the more specific a problem is, the clearer it is which profession is responsible for solving it. Hence, strengthening awareness collaboratively may overcome the dilemma. Also, it is necessary to reconstruct a curriculum based on the premise of interprofessional activities.